ANALYSIS OF STUDENTS' CRITICAL THINKING ABILITY IN GLOBAL WARMING MATERIALS AT SMA PGRI 2 PALEMBANG - Murniati Murniati (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2023)
This study aims to determine the level of students' critical thinking skills on global warming material. His research method is descriptive quantitative, namely explaining what is by using statistics. The research population was all students of class XII SMA PGRI 2 Palembang, using a purposive sampling technique as samples were students of class XII-IPA 3, which consisted of 32 students. The instrument used is in the form of critical thinking questions in the form of essays, referring to Ennis' critical thinking. Students' critical thinking abilities are grouped into Elder and Paul's thinking skills into 4 groups, namely uncritical, less critical, moderately critical and critical. The results showed that students' critical thinking skills in global warming material were low because of all Ennis' critical thinking indicators, students scored below 45%. When viewed based on the critical thinking level of Elder and Paul, students are at an uncritical level, namely TBK 0, 37.5% not critical, TBK1, 50%, less critical, TBK2, 9.4% quite critical and TBK3, 3.1% kirits. The results of the study concluded that students' critical thinking skills on global warming material needed to be improved by training students to solve a problem from various points of view.